Two-stage treatment of hip periprosthetic joint infection complicated with retroperitoneal urinary bladder defect - Sergei T. Ivanian (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Purpose To demonstrate the need for a multidisciplinary approach to the treatment of patients with deep periprosthetic joint infection (PJI) and emphasize the importance of preoperative preparation and well-coordinated work of related specialists using a specific clinical instance. Case report Reported is a successful experience of two-stage treatment of the patient with hip PJI complicated with urinary bladder defect. A 40-year old male patient diagnosed with left-sided deep hip PJI Tsukayama type 3 was treated at department of infection surgery, Rostov Regional Clinical Hospital No. 2 in January 2019. Total hip arthroplasty performed in 2008 was complicated by migration of acetabulum component. A retroperitoneal bladder defect (pressure ulcer) was detected during the first stage of resection arthroplasty and placement of an antibacterial spacer. Urological procedure was performed in a delayed manner due to technical difficulties of implant removal, prolonged and traumatic procedure, and high blood loss. With the patient's condition stabilized cystoscopy and bilateral ultrasound guided percutaneous nephroureterostomy were performed. Prolonged antibacterial aetiotropic treatment was administered. The second stage of surgical treatment included revision hip arthroplasty using a tailored acetabular component and a standard revision femoral component performed at 6 months of debridement. Results Short- and long-term results were good with sustained remission achieved. Patient could walk unassisted using a cane and had a satisfactory ROM in the left hip with HHS scored 76.255. Conclusion Multiple disciplinary teamwork is appropriate for treatment of deep PJI with much coherence, coordinated efforts and expertise from diverse professionals.